Methylome analysis and integrative profiling of human HCCs identify novel protumorigenic factors - Neumann, Olaf; Kesselmeier, Miriam; Pellegrino, Rossella; Radlwimmer, Bernhard; Hoffmann, Katrin; Ehemann, Volker; Schemmer, Peter; Schirmacher, Peter; Lorenzo Bermejo, Justo; Longerich, Thomas (Hepatology, 2012)
To identify new tumor-suppressor gene candidates relevant for human hepatocarcinogenesis, we performed genome-wide methylation profiling and vertical integration with array-based comparative genomic hybridization (aCGH), as well as expression data from a cohort of well-characterized human hepatocellular carcinomas (HCCs). Bisulfite-converted DNAs from 63 HCCs and 10 healthy control livers were analyzed for the methylation status of more than 14,000 genes.
First published: 11 June 2012
Gesehen am 15.06.2018